Ripples and Wrinkles in Graphene: Beyond Continuum Mechanics - Melo-Hurtado, F; Elettro, H (Springer International Publishing, 2019)
Frontal polymerization (FP) or vitrification consists in the generation of a reaction front, in a localized sector of the material, that travels in a particular direction. Their remarkable flexibility permits to controllably polymerize materials with different molecular weights and variable chemical nature. One of the advantages of FP is that it is possible to generate thin layers of a polymerized material over an unpolymerized composite, being suitable for creating wrinkled patterns in homogenous polymeric materials. In this chapter, the main types of frontal polymerization are described, as well as several examples and applications which take advantage of this methodology to form wrinkled patterns of variable materials. © Springer Nature Switzerland AG 2019.